Effect of Schroth Rehabilitation Exercise Program on Scoliometer Readings, Lumbar Lordosis and Calcaneal Valgus Angle in Patients with Idiopathic Scoliosis - Jaeyong PARK; Sangho KIM; Jungchul LEE; Sung-Bum JU (Tehran University of Medical Sciences, 2020)
No Abstract